Materiality, reception and symbolism of color in the monumental sculpture of the Catalan Counties: the porticoes of Ripoll and Agramunt - Cutrina Gallart, Laia (De Medio Aevo, 2026)
For a long time, Romanesque portals were interpreted as essentially monochrome stone structures, a perception largely shaped by the present condition of the monuments rather than by their original appearance. Recent restoration campaigns, together with scientific and stratigraphic analyses, have demonstrated that many of these monuments were originally covered with pigments and metallic decorations. This article examines the role of color in Romanesque monumental portals in the Catalan Counties through the analysis of two case studies: the portal of the monastery of Santa Maria de Ripoll (mid-twelfth century) and the portal of Santa Maria d’Agramunt (1283). Combining technical evidence from restoration studies and stratigraphic analyses with the interpretation of medieval color symbolism, the article explores how pigments, gilding and sculptural form interacted to create complex visual programs and evolving chromatic surfaces. By situating these portals within a broader European context of medieval polychrome sculpture, the study demonstrates that color played a crucial role in structuring visual hierarchies and reinforcing the theological meanings of monumental portals. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back